THE RELATIONSHIP BETWEEN BODY MASS INDEX AND HEMOGLOBIN LEVELS AND ITS ASSOCIATION WITH EMPLOYEE FITNESS STATUS - Salsabilla, Dinda Anindita; Aghadiati, Faradina; Heryanda, Mahfuzhoh Fadillah; Amalliyah, Puji; Qutratu'ain, Dita Shafa (HEARTY, 2025)
Anemia is a common health problem and is often related to a person's nutritional status. This study aims to analyze the relationship between Body Mass Index (BMI) with hemoglobin (Hb) levels and its implications for the fitness status of employees. This study used a cross-sectional design with 36 employees as respondents. Data were collected through direct measurement of BMI, Hb levels using the Easy Touch GCHb tool, and fitness status with the Harvard Step Test. Analysis was conducted using the Chi-Square test. The results showed that the majority of respondents had low Hb levels (55.6%), obese BMI (52.8%), and inadeqaute fitness status (55.5%). There was a significant relationship between gender and Hb levels (p=0.003) and between BMI and Hb levels (p=0.048). However, there was no significant relationship between Hb level and fitness status (p=0.660). These findings suggest that BMI and gender affect hemoglobin levels, but hemoglobin levels are not directly related to physical fitness levels. Understanding the relationship between nutritional status and Hb levels is important for anemia prevention and fitness improvement.